Efficacy of 3% Hypertonic Saline Nebulization in Acute Bronchiolitis versus Salbutamol Nebulization: A Randomized Controlled Trial - Pradip Kishore Mazumder; Arup Dutta; Md Abdullah Al Mamun; Anwarul Azim; S M Zahed Kamal; Mohammad Toufiq Ul Alam; Parmita Paul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Acute bronchiolitis is a leading cause of hospitalization in infants, often managed with bronchodilators and supportive care. Hypertonic Saline (HS) has emerged as a potential therapy, but its efficacy compared to salbutamol remains debated. The aim of the study is to compare the efficacy of 3% Hypertonic Saline (HS) nebulization versus salbutamol nebulization in reducing hospitalization dura tion and clinical severity in infants with acute bronchiolitis. Materials and methods: A Randomized Controlled Trial (RCT) was conducted at BGC Trust Medical Collee Hospital, Chattogram from January 2022 to December 2023, involving 200 infants (100 cases, 100 controls) diagnosed with bronchiolitis (WHO criteria). Patients were randomized into two groups: Group I (3% HS, 4 mL nebulized every 6 hours) and Group II (0.3ml salbutamol diluted in 3 mL normal saline every 6 hours). Clinical severity was assessed using the Respiratory Distress Assessment Instrument (RDAI) and Wang Clinical Severity Score (CSS). Results: The mean hospitalization duration was significantly lower in the HS group (3.5 ± 1.2 days) vs. salbutamol (4.8 ± 1.5 days, p < 0.001). Mean CSS improved more in the HS group at 24 and 48 hours (p < 0.05). Adverse events (Tachycardia, tremors, restlessness) were more frequent in the salbutamol group (p < 0.01). Conclusion: Nebulized 3% hypertonic saline significantly reduces hospitalization duration and clinical severity in bronchiolitis compared to salbutamol, with fewer adverse effects. It should be considered as a first-line therapy for acute bronchiolitis. Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 81-85